Effects of Carbonization Temperature and Component Ratio on Electromagnetic Interference Shielding Effectiveness of Woodceramics - Yubo Tao (Materials, 2016)
Woodceramics were fabricated in a vacuum through carbonization of wood powder impregnated with phenol formaldehyde (PF) resin. The effects of carbonization temperature and mass ratio of wood/resin on electromagnetic interference (EMI) shielding effectiveness (SE) and morphology of woodceramics were explored. The PF resin made wood cell walls have the characteristics of glassy carbon. Wood axial tracheid and ray cells were filled with more glassy carbon by increasing addition of PF resin. Moreover, the increase of carbonization temperature was beneficial to improving SE. Woodceramics (mass ratio 1:1) obtained at 1000 °C presented a medium SE level between 30 MHz and 1.5 GHz.